Spatio-Temporal Typology of Land and Forest Fire in Sumatra - Israr Albar; I. Nengah Surati Jaya; Bambang Hero Saharjo; Budi Kuncahyo (Institute of Advanced Engineering and Science, 2016)
The characteristic of land and forest fires occurred in Indonesia are varied widely, following the variation of time within a year and geographic location. This paper describes how the spatio-temporal of forest and land fire typology was developed. The main objective of this study was to develop a spatio-temporal typology of forest and land fire by considering several key indicators that directly related to the density of active fire occurrence, such as percentage of forest area (x1), population density (x2), ratio of forest area to population (x3), ratio of plantation area to population (x4), ratio of agriculture area to population (x5), GRDP (x6), population growth (x7), deforestation growth (x8), plantation growth (x9) and dry agriculture growth (x10) as well as MODIS-based fire hotspot. The typology analysis was performed using clustering techniques with Euclidean distance dissimilarity measure, where the grouping process was drawn with single linkage method. The temporal analysis showed that the highest occurrence of the fire hotspot was mainly found in the third quarter. It was found that the forest and land fire typology could be developed into three classes using variables x6 and x7 with overall accuracy of 78.15% or x1-x6-x7 with overall accuracy of 78.8%. No accuracy improvement was obtained when the typology was developed using five variables x1-x3-x4-x6-x7.